Baroclinic instability from an experimental perspective - Harlander, Uwe; Kurgansky, Michael V.; Speer, Kevin; Vincze, Miklos (Comptes Rendus. Physique)
In the mid-latitude atmosphere, synoptic eddies carry heat and momentum towards the poles and are hence a major element shaping weather and climate. The eddies are due to baroclinic instability caused by a supercritical vertical wind shear, which in turn is due to a supercritical meridional temperature gradient. Since the 1950s this crucial instability has systematically been studied with the thermally driven rotating annulus laboratory experiment. In this review, we summarize the research on baroclinic instability from the experimenter’s perspective covering a period of about three quarters of a century. The fact that it was possible to tie in with the field of atmospheric dynamics, right from the start in the 1950s, makes the experiment unique compared to other experiments representing geophysical flow phenomena. The applications span a wide range of topics, e.g., regime transitions and the route to turbulence in the presence of rotation, or geostrophic turbulence, internal wave generation at baroclinic fronts, tests of operational weather forecasting methods, extreme value distributions with regard to climate, and more. In view of new measurement methods and data processing techniques, the baroclinic instability experiment will continue to be an important complement to numerical methods in the future.